Neurostructural correlates of retinal microvascular caliber in adolescent bipolar disorder - Megan Mio; Kody G. Kennedy; Mikaela Dimick; Alysha Sultan; Lisa Fiksenbaum; Beth Selkirk; Peter Kertes; Brian W. McCrindle; Sandra E. Black; Bradley J. MacIntosh; Benjamin I. Goldstein (Wiley, 2021)
Abstract Objectives Vascular‐brain associations are well established in adults but neglected in youth and psychiatric populations, who are at greater cardiovascular risk. We therefore examined the association of retinal vascular caliber with regional brain structure in adolescents with and without bipolar disorder (BD). Methods One hundred and three adolescents (n = 51 BD, n = 52 healthy control [HC]) completed retinal fundus imaging, yielding arteriolar and venular diameters, followed by T1‐weighted 3‐Tesla MRI. Region of interest (ROI) analyses examined ventrolateral prefrontal cortex (vlPFC) and ventromedial prefrontal cortex (vmPFC), anterior cingulate cortex (ACC), amygdala, and hippocampus, complemented by vertex‐wise analyses. Linear regression assessed the association between retinal measures and brain structure, adjusting for covariates including age, sex, BMI, and intracranial volume (ICV). Results In the overall sample, arteriolar caliber was negatively associated with ACC volume (β = −0.20, puncorrected = .046) and surface area (β = −0.19, puncorrected = .049). There were no other significant ROI findings. Vertex‐wise analyses detected several significant positive bilateral associations of arteriovenous ratio (AVR) with volume and surface area in regions including rostral middle frontal gyrus (left p = .001; right p = .006), isthmus cingulate cortex (left and right p < .001), and left precuneus (p < .001). Significant negative associations were also observed for AVR (p = .03) and arteriolar caliber (p = .01), including a cluster encompassing the left rostral middle frontal gyrus and orbitofrontal cortical thickness. In the sole retinal‐by‐diagnosis interaction, greater AVR was more strongly associated with lower volume in the left middle temporal and fusiform gyri in BD versus HC (p = .004). Conclusion This study provides evidence that vascular‐brain associations are already evident in adolescence, suggesting that optimizing cardiovascular health may benefit the brain. This may be particularly relevant in BD and other brain disorders. Future research focusing on subpopulations where vascular‐brain associations may be especially strong, for whom vascular‐related interventions may be most indicated, is warranted.